1975
DOI: 10.1111/j.1399-0039.1975.tb01484.x
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the HL-A System in Khoisan Populations of South West Africa

Abstract: Work supported in part by the South African Institute for Medical Research, the Chris Barnard Fund and a grant from the U.K. Medical Research Council. Also the J. A. Cohen Institute for Radiopathology and Radiation Protection (IRS), the National Institute of Health (Contract PH 43‐65‐992), the Dutch Organisation for Health Research (TNO), the Dutch Foundation for Medical Research (FUNGO) and the Dutch Organisation for the Advancement of Pure Research (ZWO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…As chairman of the Kalahari Research Committee, Tobias initiated a series of multidisciplinary expeditions to study the Kalahari San between the years (Tobias, 1966, 1972a, 1975a. These expeditions embraced physical anthropology, demography, and ecology, under the writer (1956, 195y7, 1961b, 1962, 1964) and Hertha de Villiers (1961, 1969a; human population genetics under Trefor Jenkins, George T. Nurse, and many collaborators in a series of field studies which continued well after the Kalah q i Research Committee ceased to operate in the 1970s (Jenkins, 1965(Jenkins, ,1968(Jenkins, ,1972Jenkins and Cleaton-Jones, 1966;Jenkins and Steinberg, 1966;Jenkins et al, 1968Jenkins et al, , 1970Jenkins et al, , 1971Jenkins et al, , 1975 Nurse, 1974, 1976; Jenkins, 1974, 1977a,b;Nurse et al, 1975); physiological adaptability, under Cyril Wyndham (Wyndham and Morrison, 1956, 1958;Ward et al, 1960; Wyndham et al, 1964a;Wyndham, 1965); psychological testing under Helmuth Reuning (1959) and Wendy Wortley (Reuning and Wortley, 1973); parasitology by Hans-Joachim Heinz (1961); and odontology under J.F. van Reenen (1961 and odontology under J.F.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…As chairman of the Kalahari Research Committee, Tobias initiated a series of multidisciplinary expeditions to study the Kalahari San between the years (Tobias, 1966, 1972a, 1975a. These expeditions embraced physical anthropology, demography, and ecology, under the writer (1956, 195y7, 1961b, 1962, 1964) and Hertha de Villiers (1961, 1969a; human population genetics under Trefor Jenkins, George T. Nurse, and many collaborators in a series of field studies which continued well after the Kalah q i Research Committee ceased to operate in the 1970s (Jenkins, 1965(Jenkins, ,1968(Jenkins, ,1972Jenkins and Cleaton-Jones, 1966;Jenkins and Steinberg, 1966;Jenkins et al, 1968Jenkins et al, , 1970Jenkins et al, , 1971Jenkins et al, , 1975 Nurse, 1974, 1976; Jenkins, 1974, 1977a,b;Nurse et al, 1975); physiological adaptability, under Cyril Wyndham (Wyndham and Morrison, 1956, 1958;Ward et al, 1960; Wyndham et al, 1964a;Wyndham, 1965); psychological testing under Helmuth Reuning (1959) and Wendy Wortley (Reuning and Wortley, 1973); parasitology by Hans-Joachim Heinz (1961); and odontology under J.F. van Reenen (1961 and odontology under J.F.…”
mentioning
confidence: 95%
“…It was a prime objective of these early studies to establish the bloodgroup pattern of various southern African populations and a subsidiary objective to determine whether the "Bantu" (South African Negro) constituted a "homogeneous race. "In the last quarter of a century considerable advances in the serogenetic appraisal of Southern African peoples were chalked up by the combined efforts of Robert W. Charlton and Thomas H. Bothwell (1959); Buckwalter et al (1961); Ralph E. Bernstein (e.g., 1963); Trefor Jenkins and George T. Nurse and their collaborators (e.g., Jenkins, 1963Jenkins, , 1972Jenkins, , 1982 Nurse, 1974,1976;Jenkins and Brain, 1967;Jenkins and Dunn, 1981; Jenkins and Cornfeld, 1972;Jenkins et al, 1968Jenkins et al, , 1971Jenkins et al, , 1975Jenkins et al, , 1978Jenkins et al, , 1980Nurse, 1977;Nurse et al, 1975Nurse et al, , 1976Nurse et al, , 1977Nurse et al, , 1978Nurse et al, , 1982Nurse et al, , 1985aNurse and Jenkins, 1973, 1977aWade et al, 1967;Chasko et al, 1979;Tipler et al, 1982; Jenkins, 1984, 1985); Alan N. Smith and C.G. Anderson of Johannesburg; H.W.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Considerable data are now available concerning HLA antigen frequencies in populations from Europe and North America, but there are relatively few studies of African negroid populations. For the class I antigens only, information is available for: San and Khoikoi of South West Africa (Botha et al 1972), Zambians (Festenstein et al 1972a), Congolese (Govaerts et al 1972), Zuluspeaking Blacks in South Africa (Brain & Hammond 1972), Ugandans , Khoisans of South West Africa (Nurse et al 1975), Tanzanians (Osoba et al 1979) and Tanzanians and Kenyans (Hall et al 1982). There is no extensive study to date on HLA antigens of Nigerian populations, although a study of 225 Yorubas tested for a limited number of antigens has been reported (Famuyiwa et al 1982).…”
mentioning
confidence: 99%
“…These groups, Zambians, Congolese, Central and North Bushmen, Hottentots and Heikum, are, among themselves, heterogeneous for some HLA alleles, as are the Bantu groups (see also Bodmer et al 1972). Some of these Black African populations are physically and culturally distinct from the Negroes of Central and West Africa (Nurse et al 1975). In addition to these studies there have been recent investigations of possible disease associations of Burkitt's Lymphoma with HLA in population samples from Kenya and Uganda (Bodmer e t al.…”
mentioning
confidence: 99%